On the Self-Intersection Local Time of Subfractional Brownian Motion. (13th December 2012) - Liu, Junfeng; Peng, Zhihang; Tang, Donglei; Cang, Yuquan
Abstract : We study the problem of self-intersection local time of d -dimensional subfractional Brownian motion based on the property of chaotic representation and the white noise analysis.